Reading comprehension strategies: a case study in a bilingual high school (2009)
Comprehension is the main purpose of reading and involves three factors: the reader, the text, and the context in which the text is read. However, not everybody reaches comprehension. Perhaps there is a lack of interest from the reader, the text is not appropriate or simply the reader does not use the strategies needed to obtain meaning. Being aware of reading comprehension strategies will make students become effective readers thanks to cognitive, metacognitive and sociaffective processes. This paper describes the methodology applied to identify the reading strategies used by bilingual students in high school and the interpretation of data obtained in a first approach. Also, it shows the future work needed to validate the data from the questionnaries applied.